2011
DOI: 10.1177/0950017010389242
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s aspirations for education, work, family and leisure

Abstract: Young people are arguably facing more ‘complex and contested’ transitions to adulthood and an increasing array of ‘non-linear’ paths. Education and training have been extended, identity is increasingly shaped through leisure and consumerism and youth must navigate their life trajectories in highly individualised ways. The study utilises 819 short essays compiled by students aged 14–16 years from 19 schools in Australia. It examines how young people understand their own unique positions and the possibilities op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
5
44
1
3
Order By: Relevance
“…Consistent with other Australian samples (Johnstone & Lee, ; McDonald et al, ; Thompson & Lee, ), respondents overwhelmingly indicated a wish to replicate traditional, socially conservative adult lifestyles in the future. Both men and women indicated that they would like to be employed, mostly full‐time and mostly in professional or skilled occupations, to be married, to be parents, and to have high levels of education.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with other Australian samples (Johnstone & Lee, ; McDonald et al, ; Thompson & Lee, ), respondents overwhelmingly indicated a wish to replicate traditional, socially conservative adult lifestyles in the future. Both men and women indicated that they would like to be employed, mostly full‐time and mostly in professional or skilled occupations, to be married, to be parents, and to have high levels of education.…”
Section: Discussionsupporting
confidence: 64%
“…This exemplifies the fact that the individual's decisions do not depend solely on their attitudes and cultural background but "it must be acknowledged that the new economy is failing to create long-term employment stability for a significant number of young people" (Furlong 2006: 567). Discontinuous trajectories can be the outcome of structural constraints among the less favoured and not only the expression of choice (McDonald et al 2011). Therefore, an approach which is more sensitive to societal transformations and social inequalities is needed to study the NEET phenomenon.…”
Section: Youth Trajectories Individual Choice and Welfare Regimementioning
confidence: 99%
“…c) Out-group and dissociative group identification and evaluation According to the theory of gendered prejudice McDonald [92], men's prejudice can be defined by aggression and dominance over groups, whereas women's prejudice can be defined by wariness and fearfulness of out-groups, mainly with regard to men as their out-group. Further, Locke, K.D.…”
Section: The Role Of Social Projectionmentioning
confidence: 99%